EXTENSIVE READING FOR INDONESIAN UNIVERSITY STUDENTS: AN ALTERNATIVE FRAMEWORK FOR IMPLEMENTATION - Yulia, Made Frida (LLT Journal: A Journal on Language and Language Teaching, 2018)
Due to the minimum language exposure that EFL learners have, one recommended way to promote interest in foreign language reading is through Extensive Reading. This kind of reading has gained popularity over the years, ever since it was introduced to the realm of foreign language learning. It has been shown to bring a lot of benefits for L2 learners in many respects, and, consequently, it has been implemented in a variety of contexts. However, the implementation of Extensive Reading has sometimes been criticized for its not observing the outlined principles, for instance, in the issues of the absence of pleasure in its undertaking and the inclusion of inappropriate post-reading activities. This paper aims at revisiting Extensive Reading along with its pertaining principles. In addition, it proposes an alternative framework to implement Extensive Reading with Indonesian EFL university students. It will specifically cast some light on how to implement supervised (or instructed) Extensive Reading.